2021
DOI: 10.1186/s43055-021-00453-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of adding T2 mapping sequence to the routine MR imaging protocol in the assessment of articular knee cartilage in osteoarthritis

Abstract: Background This work aims at elucidating the role of adding complementary T2 mapping to the routine 1.5 Tesla MRI protocol in the articular knee cartilage assessment for early detection of osteoarthritis, and also, comparing the articular cartilage thickness and T2 relaxation times between the case and control groups regarding knee compartments affection. Results Both sensitivities and specificities were 73.3% and 100%, respectively, for the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…In addition, no correlation could be seen between age and T2/T2* values, although some other studies found increasing T2 and T2* parameters with age, especially in the medial compartment of the knee. 7,47,48 We found no significant intergroup changes regarding the progression of morphological cartilage degeneration. Progression was overall little to moderate over 12 months in our study cohort, which is similar to previous studies.…”
Section: Table 5 Number Of Available Mr Scans For Evaluation In Each ...contrasting
confidence: 52%
“…In addition, no correlation could be seen between age and T2/T2* values, although some other studies found increasing T2 and T2* parameters with age, especially in the medial compartment of the knee. 7,47,48 We found no significant intergroup changes regarding the progression of morphological cartilage degeneration. Progression was overall little to moderate over 12 months in our study cohort, which is similar to previous studies.…”
Section: Table 5 Number Of Available Mr Scans For Evaluation In Each ...contrasting
confidence: 52%
“…Likewise, assessing these parameters can help detect early OA, i.e., when the damage may still be reversible [7,8]. T2 mapping, when added to the clinical routine protocol, increased the sensitivity of detecting early OA [9,10]. However, the clinical adoption of T2 and T1ρ mapping techniques is, among other factors, impeded by their long acquisition times, which may take 10 min or more to cover the whole joint [11].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative MRI techniques such as T2 or T1ρ mapping may be beneficial in detecting such changes at a potentially reversible stage [ 5 , 6 ]. Consensus prevails that adding T2 maps to the routine knee protocol improved sensitivity in detecting cartilage lesions significantly [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative MRI techniques such as T2 or T1ρ mapping may be beneficial in detecting such changes at a potentially reversible stage [ 5 , 6 ]. Consensus prevails that adding T2 maps to the routine knee protocol improved sensitivity in detecting cartilage lesions significantly [ 3 , 6 ]. The literature is less clear on T1ρ: even though the association between cartilage degeneration and prolongation of T1ρ relaxation is well established [ 7 , 8 ], its potential diagnostic benefits remain to be ascertained.…”
Section: Introductionmentioning
confidence: 99%